Between text and practice: an assessment of al-fida among the yoruba muslims of South West Nigeria (2012)
Studies have been conducted in the area of death and funerary rites in Islam. However, there is a dearth of research in the area of organizing al-fida' programs among the Yoruba Muslims of South West Nigeria. Therefore, this paper attempts to fill the gap. The paper examines the local practice of al-fida' in Yorubaland as against the background of the universally accepted orthodox Islamic teachings and practices on post-funerary duties of Muslims to the dead. It also traces the areas of likely influence of the African Traditional Religion on some Yoruba Muslims in the area of post-funerary rituals. Key-informant interviews were conducted with purposively selected Yoruba Islamic scholars. The study discovered that some Yoruba Muslims who engage in al-fida' “ceremonies” may have deviated from the pristine Islamic tradition and unconsciously imitate the adherents of African Traditional Religion in the land.